Voicing Confidence: A Narrative Inquiry into Indonesian EFL Students' Experiences with the SpeechAce Pronunciation Tool - Mustagis, R Muhammad Satria Gyas; Muljanto, Setia (IKIP Siliwangi, 2026)
This qualitative investigation examined pronunciation learning experiences among four male Indonesian EFL students who obtained high scores exceeding 7.0 using SpeechAce technology within a Pronunciation Practice 2 course at Institut Pendidikan Indonesia Garut. Employing narrative inquiry methodology and Labov's analytical framework, researchers systematically analyzed self-reflection documents to understand participants' developmental journeys. Results demonstrated that learners progressed through transformative phases: encountering initial pronunciation challenges, implementing personalized learning strategies, experiencing emotional validation through high performance scores, and ultimately developing enhanced speaking confidence. A significant